BOB loss-preventing for modern trade retail product safety - Dulyakorn, Nitikorn; Pavaganun, Chavana; Mangalabruks, Benja; Fujii, Yusaku; Yupapin, Preechap P. (My University, 2011)
For Bottom Of Basket (BOB) Loss-preventing for Modern Trade Retails camera indicates the items of shoplifting front end theft accounts of total in-store shrink. BOB shrink is particularly hard on a store's margins since a single BOB item can often run for example, a 12-pack of paper towels, a large pack of diapers or a large box of laundry detergent. Just a single loss per lane per day can drive many profit loss for a large grocery chain. Numerous attempts have been made over the years to combat this problem, the camera and detect sensor linkage at cashier land can integrate with the POS and can recognize what the BOB items is and link it to the item's UPC. That means they can ring up items before lost and can deter collusion, and can stop cashiers from ignoring that an item is on the bottom of the cart. Lastly, this research vision outlook on next future work activity that will use GUI and orientation product-safety protection sensor to synchronization the 3D visualization with mobile explorer as a real time product protection on Modern Trade retails location.
Keywords: Innovative communication; Loss preventing; Loss property; Re-creation; Re-production